Kesadaran Hukum Masyarakat Pemalang Terhadap Pilkada Serentak Tahun 2020 di Era Pandemi Covid-19 - Imaro Sidqi (Rechtenstudent, 2020)
This paper aims to seek or develop public legal awareness and efforts to develop the Pilkada in the Covid-19 Pandemi Era. The research method used in this paper uses juridical empirical, with a qualitative approach. The data technique uses observation, interviews, and literature studies. Data checking techniques used triangulation and analysis using interactive models. The results showed that the awareness of Pemalang Regency people in the middle to lower category was still low, while people with the middle to upper category had started to have knowledge and understanding of the simultaneous regional elections and their policies and how the considerations for choosing, exercising their rights and obligations, and procedures were in the era of the Covid-19 pandemi. In addition, the attitudes and behavior of the middle to upper class society have begun to be structured, reprimanding officers who underestimate their duties. The factors that influence the legal awareness of Pemalang Regency society, namely: education, economy, religion, and socio-cultural factors. Then, efforts to build their awareness through counseling and campaigns about simultaneous regional elections, especially during the Covid- 19 pandemic.